Analysis of Islamic Religious Education Curriculum Development in General Universities in Indonesia - Alfiyah, Nur; Hanifah, Khusnul; Fatah Yasin, Ahmad; Asrori, Mohammad (Jurnal Administrasi Pendidikan Islam, 2024)
Curriculum development is a very important discourse in responding to educational challenges that are always growing and changing from time to time. This research analyzes the development of Islamic religious education curriculum of public universities in Indonesia. The research design uses a qualitative approach with literature study methods and interviews with 5 informants, namely graduate students as well as PTU alumni (at the undergraduate level) with qualitative descriptive data analysis. The results of the study revealed that: First, the Islamic religious education curriculum in Indonesian public universities is on average implemented through “Islamic Religious Education” courses as personality development and supported by religious programs designed according to the uniqueness of the university. Second, in terms of material substance, it is basically the same as Islamic religious universities, because it refers to the college curriculum guidelines, but the material presented is more essential and there are adjustments to the local culture of each university. This research concludes that the Islamic religious education curriculum of public universities in Indonesia has been well developed, but in the future it still requires innovation / renewal so that it is more cultured and integrated.